Ochratoxin A Degradation and Stress Response Mechanism of Brevundimonas naejangsanensis ML17 Determined by Transcriptomic Analysis - Zitong Zhao; Zehui Niu; Zhihong Liang (Foods)
Ochratoxin A (OTA) is a naturally occurring mycotoxin mainly produced by certain species of Aspergillus and Penicillium and is a serious threat to human health and food safety. Previous studies showed that Brevundimonas naejangsanensis ML17 can completely degrade 1 μg/mL of OTA. The aim of this study was to investigate the degradation effect of ML17 at different concentrations of OTA, and specifically, to investigate the mechanism of OTA degradation by ML17. The growth of ML17 was not affected by exposure to 6 μg/mL OTA within 24 h. ML17 could almost completely degrade 12 μg/mL of OTA within 36 h, converting it into the non-toxic OTα and L-phenylalanine. Transcriptomic analysis showed that 275 genes were upregulated, whereas three genes were downregulated in ML17 under the stress of 1 μg/mL OTA. Functional enrichment analysis showed that exposure to OTA enhanced translation, amide and peptide biosynthesis and metabolism, promoted oxidative phosphorylation, and increased ATP production. Further analysis revealed that, when exposed to OTA, ML17 exerted a stress-protective effect by synthesizing large amounts of heat shock proteins, which contributed to the correct folding of proteins. Notably, genes related to antioxidant activity, such as peroxiredoxin, superoxide dismutase, and glutaredoxin 3, were significantly upregulated, indicating that ML17 can resist the toxic effects of OTA through adjusting its metabolic processes, and the enzyme-coding gene0095, having OTA degradation activity, was found to be upregulated. This suggests that ML17 can achieve OTA degradation by regulating its metabolism, upregulating its antioxidant system, and upregulating enzyme-encoding genes with OTA degradation activity. Our work provides a theoretical reference for clarifying the mechanism of OTA degradation by ML17.